THE CONSTRUCTION OF LASER PUSH - UP TESTING MACHINE - Palivanich, Asadang (Academic Journal of Thailand National Sports University, 2024)
The research aimed to create a laser push up test. straight quality confidence and choice the target group used students who are studying at the secondary level. Ramkhamhaeng University Demonstration School in the Swimming Club subject of 30 people obtained from a specific selection. The results of the innovation test of the efficiency of the innovation of the laser push up test showed that innovation was effective in terms of the number of personnel, budget, time spent. It was found that using innovation can result in less personnel use. Budget compared to the longer lifespan on an average yearly basis, innovations cost less. compared to so many personnel to perform a test. and time to test innovations is also less than human testing. When considering the quality of innovation in various fields, it was found the validity in all 5 aspects when considering all averages, found that the instrument used was 0.80 straight. Innovation has the quality of reliability by considering the values ​​of the people who counted and the frequency counted from the innovative machines are equal. and test the multiple choice by alternating between different groups of innovative users to participate in the innovation test. It was found that the values ​​obtained from the staff were counted. and the values ​​counted with innovations are equal.